Acceptance of digital health services among older adults: Findings on perceived usefulness, self-efficacy, privacy concerns, ICT knowledge, and support seeking - Jokisch, Mario R.; Schmidt, Laura I.; Doh, Michael (Frontiers in Public Health, 2022)
Background Over the last decade, the rapid advancements in information and communication technologies (ICTs) have also driven the development of digital health services and applications. Older adults could particularly benefit from these technologies, but they still have less access to the Internet and less competence in using it. Based on the empirical literature on technology acceptance among older adults, this study examines the relations of perceived usefulness, self-efficacy, privacy concerns, ICT knowledge, and support seeking (family, informal, formal/institutional) with older adults' intention to adopt new digital health services. Methods The study included 478 older adults who participated in an online or paper/pencil questionnaire (M = 70.1 years, SD = 7.8; 38% male). Sociodemographic characteristics, subjective health status, and variables related to technology acceptance were assessed. Results Latent structural equation modeling revealed that higher perceived usefulness, higher self-efficacy regarding digital health technologies, and lower privacy concerns contributed to a higher intention to use digital health services among older adults. Contrary to our expectations, general ICT knowledge was not a significant predictor. Older adults who reported seeking more support regarding technology problems from family members and formal/institutional settings also reported higher usage intentions, whereas informal support was not as relevant. Furthermore, higher age was associated with higher perceived usefulness and lower self-efficacy. Discussion Future studies should further explore mediating factors for intention and actual use of digital health services and develop educational programs including follow-up assessments.